Blockchain for next generation services in banking and finance: cost, benefit, risk and opportunity analysis. Issue 3 (29th June 2020) - Osmani, Mohamad; El-Haddadeh, Ramzi; Hindi, Nitham; Janssen, Marijn; Weerakkody, Vishanth
Abstract : Purpose: The purpose of this paper is to help in providing a better understanding of the application of blockchain technology in the context of the banking and finance sectors. The aim is to outline blockchain's benefits, opportunities, costs, risks as well as challenges of the technology in the context of banking and finance services. Design/methodology/approach: Careful examination of the extant literature, including utilising relevant academic-based research databases has been carried out. It covered reviewing various research contributions published in peer-reviewed journals, academic reports, as well as technical reports to help in identifying related benefits, opportunities, costs and risks. Findings: The findings reveal that there are limited contributions in utilising blockchain in the banking and finance sectors when compared with other sectors. As such, the study highlighted the relevant perspective of benefits, opportunities, costs and risks within such sectors. Practical implications: This study helps in offering a focal point to banking and financial sector managers and decision-makers for realising the value and offerings of blockchain technology as well as associated strategies and programmes. Originality/value: This study highlights the need for a holistic understanding of the various aspects of cost, benefits, risk and opportunities to create blockchain applications that work for banking and finance sectors